Investigation of bacteremia following orthodontic debanding - (:unkn) unknown (ANGLE ORTHODONTISTS RES EDUC FOUNDATION INC, 2000)
The aim of this study waste investigate the prevalence of bacteremia after orthodontic debanding and debonding. The study group comprised 30 patients (10 men, 20 women). All were treated using the Edgewise technique. Patients with acceptable oral hygiene and fixed appliances in both jaws were included in the study group. Blood samples were obtained using a strict aseptic technique before and after removal of bands and brackets. A 6.6% bacteremia prevalence was observed in both preoperative and postoperative blood samples.
Keywords: bacteremia; orthodontic debanding; debanding; INFECTIVE ENDOCARDITIS; BACTERIAL-ENDOCARDITIS; ANTIBIOTIC-PROPHYLAXIS; RISK; PREVENTION; MANAGEMENT; CHILDREN; EFFICACY; PATIENT; ADULTS